Essential work of fracture of low‐filled poly(methyl methacrylate)/starch composites. Issue 3 (23rd July 2012) - Ali, S. Mohammad; Unnikrishnan, G.; Joseph, M. A.
Abstract In this study, poly(methyl methacrylate) (PMMA)/starch composites were prepared by a simple solvent casting method. The morphologies of the PMMA/starch composites were studied by scanning electron microscopy. The intermolecular interaction between PMMA and starch was investigated with Fourier transform infrared spectroscopy. The thermal properties of the PMMA/starch composites were compared with those of the pure PMMA sample. Thermogravimetric analysis showed that the thermal stability increased as the starch content increased in the composites. The biodegradability of the PMMA/starch composites was studied with a soil burial test. The degradability was measured in terms of mechanical strength, which increased as the starch content increased. The essential work of fracture (EWF) of the PMMA/starch composite films was investigated by the application of EWF theory under in‐plane (mode I) conditions, and we found that the toughness, in terms of the EWF of composites, increased compared to that of pure PMMA. The fracture of the composites was also evaluated by ANSYS software, and the results were compared to the experimental output. The increased toughness of these PMMA/starch composites may enable their application in the automobile and packaging industries. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013